AN ANALYTICAL STUDY ON PARENTERAL AND ORAL IRON THERAPY IN THE TREATMENT OF MODERATE DEGREE OF IRON DEFICIENCY ANEMIA IN PREGNANCY. - Mary P N, Almeta; Banerjee, Alaka; Nath, Pranoy; Ahmed, A.B Fuzayel; Barbhuiya, Sahidul Alam (Student's Journal of Health Research Africa, 2024)
Background Anemia, especially caused by insufficient iron and acute blood loss, is prevalent in pregnancy and the postpartum period. Iron requirements rise significantly during pregnancy to support both maternal and fetal needs. Aim: To evaluate the efficacy of Intravenous Iron and oral iron therapy in moderate degree of iron deficiency anemia in the second and third trimesters of pregnant women attending Antenatal OPD or labor room in Silchar Medical College and Hospital. Methods An Observational Cross-Sectional Study was done on 250 pregnant women attending Antenatal OPD and patients admitted to “The Department of Obstetrics and Gynecology of Silchar Medical College and Hospital” with hemoglobin 7-9.9 g/dl. 250 Population selected randomly, separated into 2 groups with 125 each. The first group of patients who were given IVIS. The second group of people received oral ferrous sulfate tablets twice daily. The patients were asked to report after 4 weeks for estimation of Hb. Results Baseline Hb of a group receiving oral iron therapy and parenteral iron therapy was 8.07 ±0.70 and 8.05±0.74 respectively. After 4 weeks of therapy, a mean difference of 0.61±0.53 was found in the oral therapy group and 1.44±0.62 in parenteral therapy where the P value is <0.001. The final rise in hemoglobin in the parenteral iron therapy group was found to be 9.47±0.97 and 8.69±0.86 in the oral receiving group. Conclusion Parenteral iron therapy was found to be an effective, safe, and alternative therapy to oral iron therapy in the treatment management of moderate degree of iron deficiency anemia in second and third-trimester pregnant women. Recommendation Further studies with newer IV iron formulations to overcome the issue of affordability and the risks of infusion-related complications and increase the sample size.